Secure IT-SDN: a secure implementation of software defined wireless sensor network. - Toledo, Cézar Murilo Geronaso de (2020)
In Software Defined Wireless Sensor Network (SDWSN), a logically centralized controller manages data flows according to high level policies, providing administrators with further control over the networks sensor behavior. Even though the Software Defined Network (SDN) paradigm brings flexibility to how Wireless Sensor Network (WSN) are managed, it also creates security issues. After all, the controller itself and sink nodes potentially becomes a central point of failure, whereas ancillary protocols may introduce new vulnerabilities into the system. In this document, possible attacks now found at SDWSN are listed, aiming to identify the main threat vectors to which the design is exposed. As a result of this analysis, a secure framework to mitigate the attacks is presented, evaluated and prevailing challenges and future research directions are discussed.